W stulecie niepodległości i „ustalonej” pisowni polskiej - Zygmunt Saloni (Ksiegarnia Akademicka Publishing, 2018)
In the Centenary of Independence of Poland and of “Fixed” Polish Spelling The unification of Polish spelling after the regaining of independence in 1918 was an important task, especially as the young state intended to build a system of public schools and introduce compulsory schooling. In view of the divergence of the so-called “Cracow” and “Warsaw” spelling at the turn of the 19th and 20th centuries, it was deemed necessary. The relevant resolution was adopted by the Academy of Learning in Cracow in 1918. Unfortunately, the official orthography was introduced with too much haste, and so it continued to be modified and amended in the following years, until a reform was passed in 1936. Later, further modifications were introduced, but not in a very clear way; first by the Language Culture Committee, then by the Polish Language Council of the Polish Academy of Sciences. The resolutions published by PLC concern details and minor issues, and have effectively no impact on how Polish is written. Generally speaking, the current Polish spelling is fixed – in its 1936 form, and petrified by long use. Usage has resisted the unskillful codification proposals.